Philippine medical thesaurus on psychiatry and psychology psychological phenomena and process in Tagalog - Bautista, Vanessa M.; Tarlit, Rodolfo Y. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This research produced an additional Philippine Medical Thesaurus on Psychiatry and Psychology in Tagalog. This time concentrating on FO2 facet-Psychological Phenomena and Processes. Using the top-down or "deductive" approach and concept of "Domain Analysis" as frameworks, data were obtained from the Medical Subject Headings (MeSH) 2005, from translation tools such as dictionaries and glossaries ranked by a linguist, and from psychiatrists, guidance counselors, and professors as respondents.
One hundred fifty-nine (159) out of two hundred thirty (230) terms were translated into Tagalog and seventy-one (71) terms do not have translations. Thesaurus proper was structured using the ISO 5964--Guidelines for the Establishment and Development of Multilingual Thesauri.
Majority of terms were found out to be compound terms; resulting to translation of compound terms in a word-for-word basis. There were also instances that a compound term has Tagalog translations coming from two different dictionaries.
This research proved the usefulness of psychology glossaries that served as remedy in translating very technical terms and no appropriate Tagalog translations. Therefore, the researcher recommends that the next researcher should try to explore the glossaries available for medicine and related fields in order to obtain the accurate translation of terms.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Filipino -- Medicine; Subject headings, Filipino -- Psychiatry; Subject headings, Filipino -- Psychology; Filipino Language -- Medical Filipino